Age and skill bias of trade liberalisation? Heterogeneous employment effects of EU Eastern enlargement - Fries, Jan (Mannheim, 2014)
"This study analyses the 2004 Eastern Enlargement to the European Union to obtain evidence on the employment effects of an increase in trade liberalisation. The Enlargement is thought to generate a trade-induced demand shock with no (or only limited) supply effects. Besides the variation over time induced by the Enlargement, identification of the effects is based on a Melitz (2003) type productivity term to differentiate firms by the extent of exposure to the demand shock. The idea is that the effects of the demand shock should be driven by differences in firm-levelp roductivity from the period before the new member countries actually entered the EU. German linked employer-employee data allow to observe the relation of initial establishment productivity with employment changes over a long panel from 1995 to 2009. The estimates show that the Enlargement had a negative effect on establishment-level employment growth, which is driven by increased worker separations and increased job destruction. Besides the overall employment effect, the study focuses on effect heterogeneity across age and skill groups of the workforce. These estimates point to a skill bias in the effect of the Enlargement that disadvantages low- and medium-skilled workers in terms of higher worker separation and job destruction. In addition, lowskilled workers suffer fewer accessions by firms, where against medium-skilled workers enjoy increased accessions and creation of new jobs. Besides this indication for a skill bias, there are no clear indications that point to an age bias in the employment effect of the Eastern Enlargement."